Accelerating Digital Maturity in Brazilian Companies: Key Recommendations - Tadeu, Hugo Ferreira Braga; Silva, Jersone Tasso Moreira; Pinheiro, Denise; Silva, Bruna Dias Diniz; Kenner, Kauã (Archives of Business Research, 2025)
This article aims to explore the maturity of the digital transformation of Brazilian companies, based on a survey carried out in 2024, analyzing different strategic dimensions and the barriers that hinder the transversal digitalization of the Brazilian territory. Furthermore, it discusses Brazil’s technological trends in relation to the global digital competitiveness landscape, offering recommendations on how the country can overcome its internal challenges and close existing gaps so that organizations can strengthen their digital initiatives and push Brazil toward a more competitive position in the global digital transformation arena.